On soliton structures of generalized resonance equation with time dependent coefficients - Tchier, Fairouz; İnç, Mustafa; Kilic, Bulent; Akgul, Ali (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
This paper integrates soliton, shock and singular solutions for the generalized long-short wave resonance equations with time dependent coefficients. We obtained several types of solitons of the mentioned equation. It is illustrated that the examined dependent coefficients are effected the speed of the wave. The first integral method (FIM) and ansatz method are applied to reach the soliton solutions of this equation. These solutions may be useful and desirable to explain some nonlinear physical phenomena. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: FIM; Generalized resonance equation; First integral method; Ansatz approach